(untitled) (Journal of Educational Management, 2021)
The study examined the dynamics of leadership and teacher effectiveness in Universities. The uninspired roles played by university leadership for societal development seem to implicate the qualities of teacher effectiveness in teaching, research and community service. Teachers’ performance appears lower than expected as personal observation has shown in most institutions in Nigeria. The study adopted a correlational survey design. The sample for the study consisted of one thousand six hundred and thirty-three (1, 633) academic staff members out of the population of eight thousand six hundred and thirty-four (8, 634) academic staff members working in the thirteen public Universities in North-central Nigeria as at April 2019. The data were collected through a structured questionnaire tagged: Dynamics of Leadership and Teachers’ Effectiveness Questionnaire (DLTEQ) confirmed to be of 0.86 reliability coefficient. The data collected were analysed using mean and standard deviation to answer the research questions, and the hypotheses were tested using the Pearson Product Moment Correlation Coefficient (Pearson r) at a 0.05 significance level. The major findings of the study revealed that the dynamics of leadership are largely lacking; teachers’ effectiveness in teaching and research are lower, and there is a significant relationship between dynamics of leadership and teachers’ effectiveness in universities. It is recommended among others that University leaders should ensure the use of quality dynamic leadership skills to have a sense of mission with good interpersonal relationships, monitor frequently, et cetera considering the situation of the work environment, and the National University Commission should set urgent dynamic leadership training for University leaders through seminars and workshops for teacher effectiveness.